Valor nutricional do milho, milheto e sorgo, desempenho animal e composição do leite de vacas mestiças leiteiras - Cavalcante, Daniella de Rezende (2010)
The objective was to compare the nutritional value of corn (Zea mays L.), millet (Pennisetum glaucum (L) R. Br.) and sorghum (Sorghum bicolor L. Moench.), in dairy cows, regarding the in situ degradability of dry matter (DM), animal performance and milk composition. It used nine crossbred Holstein x Zebu cows, live weight of 570 kg which, were grouped and randomly assigned to each treatment type (silage). The experiment consisted of three periods of 22 days each and analyzed according to design scheme in three 3 x 3 Latin square. Submitted the data to variance analysis and means were compared using the test Student-Newman-Keuls (SNK), at 5% probability. DM intake as% BW ranged from 2.07% millet silage (SMILH) and sorghum (SS) to 2.58% of corn silage (MS). Averaged across periods, SMILH caused weight loss (-0.99kg/cow/day) and SS and SM gains 0.73 and 0.96kg/cow/day, respectively. SM highest yields of milk production in period 2, and SS in the third period. Milk production of SMILH was influenced lower in all periods. There was no statistical difference (P>0.05) among treatments on the concentration (%) of fat, protein, total solids, acidity and extract nonfat milk. The test of degradability in situ forages was conducted using two dry rumen fistulated crossbred Holstein x Zebu cows, (live weight of 480 kg), rumen fistulated. Incubation periods were 6, 24 and 96 hours, the time zero was estimated by washing away the bags samples in water. The experimental design was a split plot: the two animals represented the blocks, the three forages, treatments; and three hours of incubation of food in the rumen, the subplot. It used the same statistics before (analysis of variance and means were compared using the SNK test at 5% of probability) and nonlinear regression. The disappearance of DM differed among the forages from 24 hours. Corn silage showed the best results for DM degradability after the sorghum and millet respectively.